Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

16.2: Pythagorean Theorem

  • Page ID
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    Here is an analog of the Pythagorean theorems (Theorem 6.2.1 and Theorem 13..1) in spherical geometry.

    Theorem \(\PageIndex{1}\) Spherical Pythagorean Theorem

    Let \(\triangle_sABC\) be a spherical triangle with a right angle at \(C\). Set \(a=BC_s\), \(b=CA_s\), and \(c=AB_s\). Then

    \(\cos c=\cos a \cdot \cos b.\)


    Since the angle at \(C\) is right, we can choose the coordinates in \(\mathbb{R}^3\) so that \(v_C\z=(0,0,1)\), \(v_A\) lies in the \(xz\)-plane, so \(v_A=(x_A,0,z_A)\), and \(v_B\) lies in \(yz\)-plane, so \(v_B=(0,y_B,z_B)\).

    Applying, 16.2.3, we get that

    \(\begin{aligned} z_A&=\langle v_C,v_A\rangle =\cos b, \\ z_B&=\langle v_C,v_B\rangle =\cos a.\end{aligned}\)

    截屏2021-02-26 上午11.19.37.png

    Applying, 16.2.1 and 16.2.3, we get that

    \(\begin{aligned} \cos c &=\langle v_A,v_B\rangle= \\ &=x_A\cdot 0+0\cdot y_B+z_A\cdot z_B= \\ &=\cos b\cdot\cos a.\end{aligned}\)

    In the proof, we will use the notion of the scalar product which we are about to discuss.

    Let \(v_A=(x_A,y_A,z_A)\) and \(v_B=(x_B,y_B,z_B)\) denote the position vectors of points \(A\) and \(B\). The scalar product of the two vectors \(v_A\) and \(v_B\) in \(\mathbb{R}^3\) is defined as

    \[\langle v_A,v_B\rangle := x_A\cdot x_B+y_A\cdot y_B+z_A\cdot z_B.\]

    Assume both vectors \(v_A\) and \(v_B\) are nonzero; suppose that \(\phi\) denotes the angle measure between them. Then the scalar product can be expressed the following way:

    \[\langle v_A,v_B\rangle=|v_A|\cdot|v_B|\cdot\cos\phi, \]


    \(\begin{aligned} |v_A|&=\sqrt{x_A^2+y_A^2+z_A^2}, & |v_B|&=\sqrt{x_B^2+y_B^2+z_B^2}.\end{aligned}\)

    Now, assume that the points \(A\) and \(B\) lie on the unit sphere \(\Sigma\) in \(\mathbb{R}^3\) centered at the origin. In this case \(|v_A|=|v_B|=1\). By 16.2.2 we get that

    \[\cos AB_s=\langle v_A,v_B\rangle.\]

    Exercise \(\PageIndex{1}\)

    AShow that if \(\triangle_s ABC\) is a spherical triangle with a right angle at \(C\), and \(AC_s=BC_s=\dfrac{\pi}{4}\), then \(AB_s=\dfrac{\pi}{3}\).


    截屏2021-02-26 上午11.24.50.png

    Applying the Pythagorean theorem, we get that

    \(\cos AB_s = \cos AC_s \cdot \cos BC_s = \dfrac{1}{2}.\)

    Therefore, \(AB_s = \dfrac{\pi}{3}.\)

    Alternatively, look at the tessellation of a hemisphere on the picture; it is made from 12 copies of \(\triangle_s ABC\) and yet 4 equilateral spherical triangles. From the symmetry of this tessellation, it follows that \([AB]_s\) occupies \(\dfrac{1}{6}\) of the equator; that is, \(AB_s = \dfrac{\pi}{3}\).